The Effect of Audit Knowledge and Professional Skepticism on Audit Quality with Auditor Ethics as a Moderating Variable: Evidence from the Inspectorate of Gorontalo Province - Heli Wahyuni Mamonto; Usman; Mentari Rizki Sawitri Pilomonu (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study investigates the effect of audit knowledge and professional skepticism on audit quality, with auditor ethics serving as a moderating variable. A quantitative approach was employed using survey data collected from auditors at the Inspectorate of Gorontalo Province. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that audit knowledge and professional skepticism have positive and significant effects on audit quality. Auditor ethics strengthens the relationship between audit knowledge and audit quality. However, auditor ethics negatively moderates the relationship between professional skepticism and audit quality. These findings indicate that auditors with adequate knowledge and strong professional skepticism tend to produce higher-quality audits. Furthermore, ethical values enhance the effective application of audit knowledge in the auditing process. This study contributes to the understanding of factors influencing audit quality in the public sector and provides practical implications for improving auditor competence, ethical conduct, and audit performance within government institutions.